Ask Question
21 February, 04:49

Find (gOf) (3)

f (x) = 3x-2

g (x) = x^2

+1
Answers (2)
  1. 21 February, 06:06
    0
    For this case, the first thing we must do is the composition of functions.

    We have:

    f (x) = 3x-2

    g (x) = x ^ 2

    (gOf) (x) = (3x-2) ^ 2

    We now evaluate the function:

    (gOf) (3) = (3 * (3) - 2) ^ 2

    (gOf) (3) = (9-2) ^ 2

    (gOf) (3) = (7) ^ 2

    (gOf) (3) = 49

    Answer:

    (gOf) (3) = 49
  2. 21 February, 07:49
    0
    F (x) = 3x-2

    g (x) = x^2

    (g o f) (3) = ?

    (g o f) (3) = g (f (3))

    x=3→f (3) = 3 (3) - 2

    f (3) = 9-2

    f (3) = 7

    (g o f) (3) = g (f (3)) = g (7)

    x=7→g (7) = 7^2

    g (7) = 49

    Answer: (g o f) (3) = 49
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Find (gOf) (3) f (x) = 3x-2 g (x) = x^2 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers